2020
DOI: 10.1016/j.mbplus.2020.100044
|View full text |Cite
|
Sign up to set email alerts
|

Native extracellular matrix, synthesized ex vivo by bone marrow or adipose stromal cells, faithfully directs mesenchymal stem cell differentiation

Abstract: Mesenchymal stem cells (MSCs) are highly responsive to cues in the microenvironment (niche) that must be recapitulated ex vivo to study their authentic behavior. In this study, we hypothesized that native bone marrow (BM)- and adipose (AD)-derived extracellular matrices (ECM) were unique in their ability to control MSC behavior. To test this, we compared proliferation and differentiation of bone marrow (BM)-derived MSCs when maintained on native decellularized ECM produced by BM versus AD stromal cells (i.e. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Collagen types I, II, III, and IV expression was analyzed with immunofluorescence staining. All MT conditions deposited all collagen types and fibronectin, although Collagen type IV was qualitatively the most abundant of all analyzed proteins for all three MT conditions ( Figure 6 ) in line with Marinkovic et al findings [ 57 ]. In PLA and Cultispher ® S MTs, collagen type IV was localized mostly at their surface, resembling the basement membrane structure [ 58 , 59 ].…”
Section: Resultssupporting
confidence: 90%
“…Collagen types I, II, III, and IV expression was analyzed with immunofluorescence staining. All MT conditions deposited all collagen types and fibronectin, although Collagen type IV was qualitatively the most abundant of all analyzed proteins for all three MT conditions ( Figure 6 ) in line with Marinkovic et al findings [ 57 ]. In PLA and Cultispher ® S MTs, collagen type IV was localized mostly at their surface, resembling the basement membrane structure [ 58 , 59 ].…”
Section: Resultssupporting
confidence: 90%
“…However, the same study showed that particularly TGFβ1 was lost during decellularization [23]. MSC-derived ECM also have been used successfully to improve MSC growth, differentiation, and angiogenic properties [20,[24][25][26] or to modulate immune responses [27,28]. In contrast to the current study, however, MSC-derived ECM had not been used to mimic health and disease so far.…”
Section: Discussionmentioning
confidence: 61%
“…Large amounts of this collagen are deposited in the bone matrix [211] , where it can be detected in compact and trabecular bone [212] . In BM, collagen type I is mainly expressed by osteoblasts [218] but also by bone marrow stromal cells [219] , [220] including MSCs [221] . Its synthesis is regulated by several factors and cytokines.…”
Section: Collagens In the Bone Marrowmentioning
confidence: 99%